Motif pemilihan profesion keguruan dan hubungannya dengan komitmen guru terhadap pelajar - Mahani, Suman (2009)
The purpose of this study was to examine the motives for selecting the teaching profession as a career and its relation with commitment towards students among teachers in Perlis. A total of 306 teacher who are teaching at 7 selected secondary schools were involved in this study. The research tool used was in the form of a questionnaire that consists of 35 questions. To test the reliability of the instrument, a pilot test was conducted and the data analysis yielded a reliability value that was statistically acceptable. A descriptive analysis of research design was used to describe what motivates and prominent motives the teachers in selecting the teacher as a profession. To test whether motives for choosing the teaching profession as a career differ between genders, T-test was used. Data analysis revealed that there is only significant differences between both gender in intrinsic motives. Pearson Correlation was also used to test if there are significant differences between commitments toward students and intrinsic motives, extrinsic motives, altruistic motives and influential motives. The results obtained showed that there are significant relationship between the four motives and commitment towards students. On the other hand, the influential motive showed a negative relation. The findings of this study have several implications on the selection of future teachers. Therefore, several recommendations were suggested for future research.